2020
DOI: 10.1016/j.celrep.2019.12.053
|View full text |Cite|
|
Sign up to set email alerts
|

LIN28B Underlies the Pathogenesis of a Subclass of Ewing Sarcoma

Abstract: Ewing sarcoma (EwS) is associated with poor prognosis despite current multimodal therapy. Targeting of EWS-FLI1, the fusion protein responsible for its pathogenesis, and its principal downstream targets has not yet produced satisfactory therapeutic options, fueling the search for alternative approaches. Here, we show that the oncofetal RNA-binding protein LIN28B regulates the stability of EWS-FLI1 mRNA in~10% of EwSs. LIN28B depletion in these tumors leads to a decrease in the expression of EWS-FLI1 and its di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…For example, lncRNA NEAT1 is stabilized by LIN28B protein in ovarian cancer (Wu et al, 2018). Similarly, LIN28B increases EWS-FLI1 mRNA stability in Ewing sarcoma (Keskin et al, 2020). However, whether LIN28B regulates circRNA stability remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA NEAT1 is stabilized by LIN28B protein in ovarian cancer (Wu et al, 2018). Similarly, LIN28B increases EWS-FLI1 mRNA stability in Ewing sarcoma (Keskin et al, 2020). However, whether LIN28B regulates circRNA stability remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…When levels of MBG are increased, levels of Fli1 decrease and a Col-1 gene promoter is released from the nucleus and procollagen-1 and collagen become activated [32]. While many studies have demonstrated that Fli1 is a pro-cancer factor [68,69], CS including MBG are becoming attractive anti-cancer drug candidates [70,71]. It is generally accepted that PE is associated with a low risk of cancer, which is not surprising considering that endogenous levels of MBG and other CS are dramatically increased in PE patients [27,28] and therefore suppress the growth of tumors in vivo and in vitro [72][73][74].…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%
“…When levels of MBG are increased, levels of Fli1 decrease, and Col-1 gene promoter is released from the nucleus, and pro-collagen-1 and collagen become activated [32]. While many studies demonstrate that Fli1 is a pro-cancer factor [57,58], CS, including MBG, are becoming attractive anticancer drugs [59,60]. It is generally accepted that PE is associated with a low risk of cancer, which is not surprising considering that endogenous levels of MBG and other CS are dramatically increased in PE patients [27,28] and therefore suppress the growth of tumors in vivo and in vitro [61,62,63].…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%
“…This phenotype was consistent with a role of Fli1 as a regulator of vessel maturation, thus, in rats following subtotal nephrectomy, elevated MBG led to a reduction in the level of Fli1 and an increase in collagen-1 level in the myocardium, and single administration of monoclonal anti-MBG antibody rats produced an antifibrotic effect, that is, restored Fli1 levels and reduced collagen-1 abundance in the myocardium [38]. Fli1 attracted attention primarily because of its contribution to different types of cancer including, gastric cancer, Burkitt lymphoma, breast cancer, pancreatic ductal adenocarcinoma, small cell lung cancer, and Ewings sarcoma [57,74,75,76]. We observed extremely high levels of MBG, low levels of Fli1, along with a very extremely high level of collagen-1 level in patients and experimental animals with preeclampsia, chronic renal failure, and malignant hypertension [33,37,38].…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%